Rehabilitasi Pasien Stroke Dimasa Pandemi Covid-19: Integrative Review - Ganut, Felisima; Arafat, Rosyidah; Hariati, Suni (LPPM Hang Tuah Pekanbaru, 2023)
Background: Rehabilitation services for stroke patients decreased during the Covid-19 pandemic, and patients mainly stayed home without rehabilitation. As a result, the patient experiences recurrent strokes, contractures, malnutrition, decubitus, and reduced cognitive function. Therefore, the repair is crucial to achieving maximum recovery and improving one's physical, mental, social, and speech abilities. Purpose: To find out the rehabilitation for stroke patients during the Covid-19 pandemic. Method: This review used a modified version of the integrative review research methodology developed by Whittemore and Knafl (2005). The literature search was conducted on five databases, namely PubMed, Science Direct, ProQuest, Cochrane Library, and DOAJ, with inclusion criteria in English, focusing on the rehabilitation of stroke patients, the Covid-19 pandemic, and original research published between 2020 and 2022. Evaluation of publications used Bowling's critical assessment model (2001). Results: Ten articles were included in the analysis. As a result, an overview of the rehabilitation of stroke patients during the Covid-19 pandemic was obtained, which included, first: Changes in the rehabilitation service system. Second: the obstacles to the rehabilitation of stroke patients during the Covid-19 pandemic, such as increasing family workload, lack of social support, and economic factors/financial constraints. Third: Changes in the functional status of stroke patients.Conclusion: The overview of the rehabilitation of stroke patients during the Covid-19 pandemic includes changes in the rehabilitation service system, obstacles to the restoration of stroke patients during the COVID-19 pandemic, and changes in the functional status of stroke patients.